(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
A dividend is a distribution of a portion of a company’s profits to its shareholders. Acompany’s dividend policy is one of its most critical pillars. One of the primary functions of dividendpolicy is to communicate with existing shareholders and to entice potential new shareholders to thecompany. The choice to pay a dividend sets the proportion of profits distributed to shareholders andthose kept by the company. The company’s dividend policy is vital since it can have a significant impacton the value of its stock and its overall success. Dividend policy is an important part of corporatefinance since it is used to send messages to shareholders about the company’s health and futureprospects. The firm’s dividend policy will dictate how the company’s profits are dispersed. Either thecompany reinvests the money or distributes a portion of the earnings to the stockholders. The value ofinvestors and the market price of shares are both increased when corporate managers employ aneffective framework of dividend decision, which is one of the fundamental tenets of financialmanagement. The market value of a company’s shares is heavily influenced by dividends, which arelargely described as financial rewards to shareholders in the form of profit distribution. The dividendpayout ratio and the amount of earnings retained by a company are directly related to the dividendchoice made by the company, which is determined by the firm’s dividend policy. With less money goingout as dividends, the corporation will have more money to reinvest. Different factors, such as firm size,ownership, and other factors, influence the dividend decision. Investment possibilities, profitability,regulatory limits, liquidity, control, and inflation are among the other essential aspects that definedividend policy and contribute to an effective dividend decision based on shareholder return andcompany value.